Ancillary Prospects of the Denatured Soil From Waterlogged Areas of Indira Gandhi Canal Scheme in Hanumangarh District of Rajasthan State, India - GUPTA, PANKAJ; SHARMA, SUDHANSHU; SHARMA, SANJAY (Asian Journal of Chemistry, 2010)
The authors performed the physical and chemical analysis and explored the useful prospects of the denatured waterlogged/saline soil. The use of scrapped soil as fillers for active components of the fertilizers was also performed.